Recurrent Falls in People with Parkinson’s Disease without Cognitive Impairment: Focusing on Modifiable Risk Factors - Lorena R. S. Almeida; Guilherme T. Valença; Nádja N. Negreiros; Elen B. Pinto; Jamary Oliveira-Filho (Parkinson's Disease)
Falls can be considered a disabling feature in Parkinson’s disease. We aimed to identify risk factors for falling, testing simultaneously the ability of disease-specific and balance-related measures. We evaluated 171 patients, collecting demographic and clinical data, including standardized assessments with the Unified Parkinson’s Disease Rating Scale (UPDRS), activities of daily living (ADL) and motor sections, modified Hoehn and Yahr Scale, Schwab and England, eight-item Parkinson’s Disease Questionnaire, Activities-specific Balance Confidence Scale, Falls Efficacy Scale-International (FES-I), Berg Balance Scale, Dynamic Gait Index, Functional Reach, and Timed Up and Go. ROC curves were constructed to determine the cutoff scores for all measures. Variables with P<0.1 entered a logistic regression model. The prevalence of recurrent falls was 30% (95% CI 24%–38%). In multivariate analysis, independent risk factors for recurrent falls were (P<0.05) levodopa equivalent dose (OR = 1.283 per 100 mg increase; 95% CI = 1.092–1.507), UPDRS-ADL > 16 points (OR = 10.0; 95% CI = 3.6–28.3), FES-I > 30 points (OR = 6.0; 95% CI = 1.6–22.6), and Berg ≤ 48 points (OR = 3.9; 95% CI = 1.2–12.7).We encourage the utilization of these modifiable risk factors in the screening of fall risk.